Requiem for junior high school. Case study - lower secondary school exam 2012 - Marek Piotrowski (Studia z Teorii Wychowania)
The article has critically assessed the information sent to the public, including teachers, on the results of external examinations contained in the Central Examination Board (CEB) reports. Basing on the analysis of two sources of information decoded from the CEB reports and the analysis of the database containing the results of examinations, 93% of lower secondary school students, it has been showed that about half of the population "failed" the lower secondary school exam in science and mathematics. Therefore they should not continue their high school education. The analysis of data decoded from the CEB report is in line with the results obtained from 93% of students. Therefore, it is advisable to conduct similar analyzes of contemporary CEB reports on students achievement after the new primary school which is operating in the new education system after liquidation of junior high schools.